Potential of Acacia melanoxylon for Pulping - Pereira, Helena (2019)
Most of the fibre raw materials used by the pulp and paper industry are from a small number of tree species. For instance, Eucalyptus and Pinus species are the major industrial pulpwood sources obtained from forests characterized by a relatively low biodiversity. The large monoculture areas also increase environmental risks such as those related to biotic attacks or forest fires. Diversification of industrial fibre sources has therefore been a matter of research and the characterization of different raw materials has been made in view of their pulping potential. Acacia melanoxylon R. Br. (blackwood) grows well in Portugal in pure or mixed stands with Pinus pinaster Aiton, and is valued as a timber species with potential for sawmills. In addition, the wood anatomical and chemical characteristics also allow to consider the species as an alternative raw material for the pulp industry. Acacia species, with their relatively short, flexible and collapsible fibres, have potential to produce papers with good trade-offs between light scattering/tensile strength and smoothness/tensile strength, at low energy consumption in refining. The pulping and paper making potential of blackwood has been studied by several authors showing an overall good pulping aptitude under the same experimental conditions of kraft pulping as used for eucalypt pulping with pulp yields ranging between 47 and 58 %. The presence of heartwood should be taken into account because it decreases the raw-material quality for pulping due to the higher extractives content. Heartwood proportion should therefore be considered as a quality variable when using A. melanoxylon wood in pulp industries. This chapter describes the characterization of the A. melanoxylon wood pulping performance, regarding yield and kappa number, and the pulp and paper properties. The application of fast spectroscopic technologies for pulp quality determination is also described.